Migración juvenil a Estados Unidos de América en pandemia y post pandemia (2021-2023) - Flores Jaramillo, Angie Juana (2024)
The research focused on analyzing the impact of youth migration to the United States during the pandemic and post-pandemic period (2021-2023), focusing on legal and doctrinal aspects related to the barriers and challenges faced by young migrants. The problematic was based on the significant increase in Ecuadorian youth migration, driven by factors such as unemployment, economic crisis and limited educational offerings. The relevance of understanding how migration and legal policies affect these young people was highlighted. The methodology used was analytical-interpretative in approach, including surveys of 30 young Ecuadorian migrants and interviews with 5 migration experts. Techniques such as online surveys and virtual interviews were used, supported by qualitative and statistical analyses. Relevant results indicated that migration policies in the United States are perceived as complex and rigid, hindering youth migration. In addition, challenging socio-legal conditions were identified during the migration process, including detention and limited access to legal services. In terms of recommendations, the need to disseminate information on rights and services available to young migrants was raised, as well as the need to establish comprehensive reintegration programs. The importance of addressing the structural causes of migration, such as economic and social inequality, was emphasized. In conclusion, the research highlights the complexity of migration policies in the United States and the difficulties faced by young migrants. It provides recommendations to improve the protection of their rights.